Peningkatan pembelajaran table tennis melalui teknik holding bet pada siswa sekolah dasar - Nur Ahmad Muharram; Setyo Harmono (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
The aim of the research was to find out that good bet-holding techniques can improve learning table tennis in fifth grade students of SD Negeri 5 Kediri. The research method uses Classroom Action Research. The results of the research during the pre-cycle, 2 students (10%) obtained completeness and 18 students (83%) had not yet completed. In the first cycle, the average increase was 44 where 11 students (39%) had completed and 13 students (61%) had not finished. The value of student activity observation is 69%, the assessment category is classically good. Cycle II increased by 83.1 where 17 students (75%) obtained completeness, 3 students (25%) had not yet completed it and the value of student activity observation increased 94.56% in the category of excellent assessment. Cycle III increased 92 where all students as much as 25 (100%) obtained completeness and the value of student activity observations increased 97%, the assessment category was very good. It was concluded that the modification of the bet using the holding bet could increase the effectiveness of student learning in the game of table tennis for the fifth grade students of SD Negeri 5 Kediri